WARISAN INTELEKTUAL IBNU RUSYD DALAM PEMIKIRAN TEOLOGI ISLAM - Hadariansyah, Hadariansyah (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2013)
The writing was concern on Ibn Rusyds theology thought. This was interesting to be discussed because that Ibn Rusyd was not only a theologian but also a philosopher and jurist of Islam. Based on this fact, then the question arises; first, whether ibn rusyds theology was different from the other figures that only theologians alone. Second, whether his philosophical and jurisprudential view affected his theology thought. The result of this writing showed that Ibn Rusyd had unique theology thought which his philosophical and jurisprudential view affected his theology so that his theology was more rational but it was not too liberal because of his jurisprudential view.